2020
DOI: 10.1002/pbc.28186
|View full text |Cite
|
Sign up to set email alerts
|

Pure pediatric ovarian immature teratomas: The French experience

Abstract: Objective To describe characteristics and outcome of pediatric ovarian immature teratomas (IT) to better define the place of chemotherapy. Methods Children with ovarian IT enrolled in TGM95 and TGM2013 studies were analyzed. Norris grading and International Federation of Gynecology and Obstetrics staging system were used. Results Thirty‐six cases were identified with a median age of 11 years (range = 1‐18): 35 of 36 stage I (17 stage IA, 13 stage IC, and 5 stage IX), including seven patients with gliomatosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…There were excellent outcomes in the nine patients undergoing ovarian cystectomy for IT, although notably cystectomy was predominantly performed for small tumours with a low pre-operative AFP level. A retrospective study of 43 patients similarly found excellent long-term outcomes, with no cases of disease recurrence in 14 patients undergoing ovarian cystectomy [12]. However, in this group, 57% of ovarian cystectomies were followed by adjuvant therapy, whereas we found that despite only an 11% rate of adjuvant chemotherapy following cystectomy, there were no recurrences or deaths.…”
Section: Discussionsupporting
confidence: 54%
“…There were excellent outcomes in the nine patients undergoing ovarian cystectomy for IT, although notably cystectomy was predominantly performed for small tumours with a low pre-operative AFP level. A retrospective study of 43 patients similarly found excellent long-term outcomes, with no cases of disease recurrence in 14 patients undergoing ovarian cystectomy [12]. However, in this group, 57% of ovarian cystectomies were followed by adjuvant therapy, whereas we found that despite only an 11% rate of adjuvant chemotherapy following cystectomy, there were no recurrences or deaths.…”
Section: Discussionsupporting
confidence: 54%
“…French study of ovarian IT, in which there was no statistically significant difference in EFS and OS based on grade. 8 In a study by Gobel et al, grade was only a risk factor in incompletely resected tumors. 20 Newton et al showed that grade was not a significant risk factor; however, 92% of patients were stage I.…”
Section: Discussionmentioning
confidence: 96%
“…It therefore appears that grade is not a risk factor in completely resected or stage I tumors, but may be prognostic in incompletely resected and/or higher stage patients. 8,17,20 Finally, due to ongoing controversy regarding optimal clinical management, biological study of this highly underinvestigated tumor type is urgently required. 21 A recent small study of 10 ovarian IT cases (pediatric and adult) using whole-exome sequencing revealed near-diploid genomes with extensive loss of heterozygosity and an absence of mutations or oncogenic variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in pediatric POIT, surveillance in stage I of any grade is recommended and has been proven to be safe as well as to reduce chemotherapy-related adverse events [ 7 , 8 , 9 ]. Recently, a series of studies proposed that active surveillance may be acceptable in stage IA-IC POIT of any grade, regardless of whether patients are pediatric or adult [ 10 , 11 , 12 , 13 , 14 , 15 ]. Nonetheless, most of these studies have evaluated pediatric and adult patients together or included patients with different pathological subtypes of MOGCTs [ 12 , 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%